TAJDIDUN NIKAH UNTUK LEGALITAS BUKU NIKAH PERSPEKTIF MASLAHAH - Ahmad Khoirin Andi; Muhammad Holid (ASA, 2023)
According to Positive Law, pursuant to newest Law that is [Code/Law] Number 16 Year 2019 about Change of Law Number 1 Year 1974 is connubial of marriage age definition have been turned into 19 year between men age and also woman. (iii) Resistance and constraint in face of nuptials phenomenon is early evaluated from existing invitation aspect that order legislation of marriage only made by complement value after books concept of fiqh traditional. This is one of the cause less maximal it application Legislation Of contemporary Law Family Moslem in field because of by legislation content there are some which interfere in or minimize disagree with philosophic value, and yuridis of sosiologis going into effect in society majority. As for effort conducted for the meminimalisir of nuptials early that is; grow awareness at society for the importance of education at children exself and the rising generation, cultivation of education of religion for every child, and also is same activity of party with KUA District